Effect of a 12-Month Intensive Lifestyle Intervention on Hepatic Steatosis in Adults With Type 2 Diabetes - Lazo, Mariana (American Diabetes Association, 2010)
OBJECTIVE: Weight loss through lifestyle changes is recommended for nonalcoholic fatty liver disease (NAFLD). However, its efficacy in patients with type 2 diabetes is unproven. RESEARCH DESIGN AND METHODS: Look AHEAD (Action for Health in Diabetes) is a 16-center clinical trial with 5,145 overweight or obese adults with type 2 diabetes, who were randomly assigned to an intensive lifestyle intervention (ILI) to induce a minimum weight loss of 7% or a control group who received diabetes support and education (DSE). In the Fatty Liver Ancillary Study, 96 participants completed proton magnetic resonance spectroscopy to quantify hepatic steatosis and tests to exclude other causes of liver disease at baseline and 12 months. We defined steatosis >5.5% as NAFLD. RESULTS: Participants were 49% women and 68% white. The mean age was 61 years, mean BMI was 35 kg/m(2), mean steatosis was 8.0%, and mean aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were 20.5 and 24.2 units/l, respectively. After 12 months, participants assigned to ILI (n = 46) lost more weight (−8.5 vs. −0.05%; P < 0.01) than those assigned to DSE and had a greater decline in steatosis (−50.8 vs. −22.8%; P = 0.04) and in A1C (−0.7 vs. −0.2%; P = 0.04). There were no significant 12-month changes in AST or ALT levels. At 12 months, 26% of DSE participants and 3% (1 of 31) of ILI participants without NAFLD at baseline developed NAFLD (P < 0.05). CONCLUSIONS: A 12-month intensive lifestyle intervention in patients with type 2 diabetes reduces steatosis and incident NAFLD.